SPECTROPHOTOMETRIC ESTIMATION OF METFORMIN IN HUMAN PLASMA - Sri, Dr Bhavya; Fatima, Amina; Rambabu, Dr D. (Journal of Biomedical and Pharmaceutical Research, 2019)
To develop a simple, selective and sensitive spectrophotometric method and validated for the determination of metformin in human plasma. The method was applied for the determination of metformin from pharmaceutical preparations and plasma samples and after spiking with metformin. The results were checked by standard addition method. A number of pharmaceutical additives and plasma matrix did not affect the determination of metformin. The proposed method was found to be accurate and precise for routine estimation of metformin hydrochloride in human plasma. Keywords: Metformin, spectrophotometric, standard addition, plasma, pharmaceutical preparation